1979
DOI: 10.3171/jns.1979.51.4.0476
|View full text |Cite
|
Sign up to set email alerts
|

Localization in somatic sensory and motor areas of human cerebral cortex as determined by direct recording of evoked potentials and electrical stimulation

Abstract: This paper reports and illustrates in figurine style results obtained by electrical stimulation of the cortex in 20 patients and by recording of cortical evoked potentials (EPs) in 13 of these patients, whose surgery required wide exposure of the Rolandic or paracentral regions of the cortex. This study is unique in that cutaneous receptive fields related to specific cortical sites were defined by mechanical stimulation, as is done in animals, in contrast to electrical stimulation of peripheral nerves at fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
177
3

Year Published

1983
1983
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 586 publications
(199 citation statements)
references
References 35 publications
16
177
3
Order By: Relevance
“…This relationship is supported by studies examining the effects of cortical stimulation on the ventral region of M1 which primarily elicits contralateral lower facial movements (Penfield, 1937;Woolsey et al,1952;Woolsey et al, 1979;McGuinness et al, 1980;Huang et al, 1988;Triggs et al, 2005) and longstanding clinical observations which have drawn the association between prominent contralateral lower facial paresis and injury afflicting the lateral peri-central cortex of the cerebral hemisphere (Green, 1938;Symon et al, 1975;Brodal, 1981;Adams et al, 1997). However, it has also been shown that to a lesser extent, OO activation can occur following direct stimulation of M1 (Woolsey et al, 1979;Benecke et al, 1988;Cruccu et al, 1990;Roedel et al, 2001;Sohn et al, 2004;Paradiso et al, 2005) and deficits transpire in OO function following damage to M1 that are less notable than perioral deficits, but are nonetheless detectable (Kojima et al, 1997). Collectively this observation may contribute to the complex nature of facial expression and possibly add to the inherent difficulties in isolating distinct, individuated facial muscle contractions following cortical stimulation (Woolsey et al, 1952;Strick and Preston, 1979;McGuinness et al, 1980;Brecht et al, 2004;Schieber, 2004).…”
Section: Intranuclear Localization Of Oo Motor Neurons and Implicatiomentioning
confidence: 62%
“…This relationship is supported by studies examining the effects of cortical stimulation on the ventral region of M1 which primarily elicits contralateral lower facial movements (Penfield, 1937;Woolsey et al,1952;Woolsey et al, 1979;McGuinness et al, 1980;Huang et al, 1988;Triggs et al, 2005) and longstanding clinical observations which have drawn the association between prominent contralateral lower facial paresis and injury afflicting the lateral peri-central cortex of the cerebral hemisphere (Green, 1938;Symon et al, 1975;Brodal, 1981;Adams et al, 1997). However, it has also been shown that to a lesser extent, OO activation can occur following direct stimulation of M1 (Woolsey et al, 1979;Benecke et al, 1988;Cruccu et al, 1990;Roedel et al, 2001;Sohn et al, 2004;Paradiso et al, 2005) and deficits transpire in OO function following damage to M1 that are less notable than perioral deficits, but are nonetheless detectable (Kojima et al, 1997). Collectively this observation may contribute to the complex nature of facial expression and possibly add to the inherent difficulties in isolating distinct, individuated facial muscle contractions following cortical stimulation (Woolsey et al, 1952;Strick and Preston, 1979;McGuinness et al, 1980;Brecht et al, 2004;Schieber, 2004).…”
Section: Intranuclear Localization Of Oo Motor Neurons and Implicatiomentioning
confidence: 62%
“…The increased activation in motor cortex in response to CRD was unlikely due to locomotion as activity counts were extremely low during the period of distention, and without significant group differences. Neuroimaging studies in humans have associated abdominal contractions with activation of the superolateral precentral gyrus (lateral portion of motor cortex) and premotor and supplemental motor cortex [10,72]. In addition, focal stimulation of these areas, either magnetically or electrically, evokes abdominal straining [15,20,34].…”
Section: Discussionmentioning
confidence: 99%
“…The ventral limit of M1 has been reported as being situated just above the Sylvian Fissure (Woolsey et al, 1979;Corfield et al, 1999), or varying as much as 4cm dorsally (Brodmann, 1909;Urasaki et al, 1994;Geyer et al, 2000b). Similarly, the ventral limit of S1 has been shown to correspond to the same dorso-ventral position as M1, immediately caudal to M1 at the base of the postcentral gyrus (Boling et al, 2002).…”
Section: Ventral Limits Of Lpmc and Smcmentioning
confidence: 99%